Determination of riboflavin in commercial drinks using fluorescence spectroscopy / Anida Yusof - Yusof, Anida (Faculty of Applied Sciences, 2009)
Determination of riboflavin in commercial drinks using fluorescence spectroscopy as well as effect of shelf life and nature of packaging were studied. Riboflavin content was determined using single excitation-emission spectra of fluorescence measurements. The excitation wavelength at 457 nm and emission wavelength at 520 nm were used in the detection of riboflavin in the samples. Standard solution and samples was analysed by fluorescence spectroscopy (Luminescence LS-50 Perkin Elmer). All analyses were carried out in triplicates. Calibration curve of standard riboflavin was used to calculate the concentration of riboflavin in samples. It was found that riboflavin determined in sample 1 (1.36 mg/lOOmL), sample 2 (0.04 mg/lOOmL), sample 3 (0.04 mg/lOOmL), sample 4 (0.05 mg/lOOmL) and sample 5 (0.05 mg/lOOmL) is less than riboflavin stated in sample 1 (1.93 mg/lOOmL), sample 2 (0.12 mg/lOOmL), sample 3 (0.13 mg/lOOmL), sample 4 (0.12 mg/lOOmL) and sample 5 (0.12 mg/lOOmL) on the label nutrition information. As we know riboflavin is sensitive to light and easily degrade when exposed to light. When in contact with oxygen, riboflavin also degrades. All samples analysed claimed to contain riboflavin as stated on the label of the packaging. Exposed to light during storage and transportation before use, natures of packaging and shortest shelf life are the factors that contributed to degradation of riboflavin. Longest shelf life the riboflavin remains in sample is highest and shortest shelf life lowest riboflavin remains. So from the study consumer can be aware with the commercial drinks because close to expiry date the riboflavin might degrade and less that stated on label.